Peran Guru dalam Meningkatkan Minat Belajar Siswa Kelas V MIN 1 Kota Bengkulu pada Masa Pandemi Covid-19 - Septiara Dwi Putri; Inka Utami; Panut Setiono; Nani Yuliantini; Wurjinem (IAIN PAREPARE, 2021)
In the learning process it is important to have student interest in learning, but it turns out that during the Covid-19 period, student interest in learning was low due to online learning carried out at home. For this reason, this study aims to analyze the role of teachers in increasing the learning interest of class V students in online learning during the Covid-19 pandemic. This research uses qualitative research methods. The role of a teacher is very important in supporting the implementation of learning, namely the role of the teacher as a facilitator, motivator, mediator and evaluator, innovator. So with the role of the teacher, of course, it can provide motivation for students in learning so that it can increase interest in learning and also student enthusiasm for learning when participating in the online learning process. Key words: The role of teachers, interests, learning, online